Performance Improvement Techniques For WDM Optical Burst Switched Networks - Subodh Bansal , Amit Gupta (International Journal of Advanced Science and Technology, 2020)
A Survey of WDM based optical burst networks and existing contention resolution techniques ofoptical burst networks has been done by taking into account the performance metrics of each.Features of different contention resolution techniques and algorithms are listed and compared. Astudy of existing contention resolution techniques based on parameters like burst loss ratio, blockingprobability, throughput, bandwidth utilization and delay has been done. It has been observed thatOBS network architecture employing a ETLQF assembly algorithm is more effective than otherassembly algorithms. Also the network performance can be improved by combining the schedulingtechniques VT-BA and CTBR